Karakter Pendidik dalam Perspektif Pendidikan Islam - Muhammad Aufa Muis; Desri Ulfa; Fera Eliza; Vivi Juliana; Amiddana Silfia (Journal on Education, 2023)
This article discusses the Character of Educators in the Perspective of Islamic Education. Basically, Islamic education is a process that takes place continuously and flows in human life and then lasts throughout life. Educators are people who play a very important role in educating the nation's children. When we talk about educators, what comes to our minds are adults who guide us and give us things we don't know to know. To become a professional educator, you must fulfill the requirements as an educator in carrying out your duties as an educator. The role of teachers in developing students to become human beings with character is very much needed as role models and role models. The research was carried out using the library research method, namely by describing theories according to experts regarding the Character and Scope of Islamic Education